Ptotic Gall Bladder with Hepatic Masses: A Case Report. (11th February 2013) - Aydin, Hasan; Aydin, Z. Banu; Hekimoğlu, Baki; Görmeli, Ayşe
Abstract : Gall bladder (GB) may be found in a variety of abnormal positions. Most of them are due to arrested development of embryonic growth at different stages. A 63-year-old female patient was admitted to our radiology unit for magnetic resonance imaging (MRI) of the liver for the lesions identified in abdominal ultrasonography (US) and computed tomography (CT). MRI showed that there was a lobulated heterogenous mass in the left lobe of the liver and a smaller one in the right lobe of the liver with the same appearance. The inferior pole of the liver was located in the pelvic space, and the GB, which contained sludges and stones, was lying down to the upper pelvic space. Hepatic masses were considered to be hemangiomas, and GB was diagnosed as ptotic GB with luminal sludge and stones. In this case, especially, MR imaging helped the surgeon to plan a proper approach to the GB in abnormal localization.